Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Variability in snow layering and snow chemistry in the vicinity of two drill sites in western Dronning Maud Land, Antarctica - Hansson, Margareta; Holmlund, Per; Karlöf, Lars; Stenberg, Malin (Annals of Glaciology, 1999)
As part of the pre-site survey in Dronning Maud Land for the European Project for Ice Goring in Antarctica (EPICA), the spatial variability of snow-layer thickness and snow chemistry was studied at two geographically different ice-core drill sites. The study aimed to quantify error bars on accumulation rates derived from firn and ice cores. One site is located on the polar plateau at Amundsenisen (76° S, 8° W) and the other in the coastal area at Maudheimvidda (73° S, 13° W). Medium-deep ice cores (100 m) and shallow firn cores (10-20 m) were drilled and snow pits (0.5-2 5 m) were dug at each site. At Amundsenisen a large (16 m x 6 m x 2.5 m deep) snow pit was dug. Snow structure in this large snow pit was mapped using optical surveying equipment, and photographically documented. Samples for analysis of nine ions and oxygen isotopes were collected along one depth profile. Density and in situ electrical conductivity measurements were made along three depth profiles! Snow-layer variability was studied in two different areas and at two different scales. At a regional scale, measured by snow-radar soundings, the variability was 8% on the polar plateau and 45% in the coastal area. The variability at a micro-scale in the large snow pit was 9%. The results indicate that ice cores from the polar plateau are more representative for a larger area than ice cores drilled in the coastal area There is no doubt that there are significant error bars on high-resolution accumulation data received from firn and ice cores, especially from the coastal area, but averaging over tens of years reduces the error in accumulation estimates.
Keywords: Dronning Maud Land; fysisk geografi; geokjemi; glasiologi; iskjerner; paleoklimatologi

Predicted present-day evolution patterns of ice thickness and bedrock elevation over Greenland and Antarctica - Huybrechts, Philippe; Le Meur, Emmanuel (Polar Research, 1999)
This paper discusses predicted evolution patterns of present-day changes of ice thickness, surface elevation, and bedrock elevation over the Greenland and Antarctic continents. These were obtained from calculations with dynamic 3-D ice sheet models which were coupled to a visco-elastic solid Earth model. The experiments were initialized over the last two glacial cycles and subsequently averaged over the last 200 years to obtain the current evolution. The calculations indicate that the Antarctic Ice Sheet is still adjusting to the last glacial-interglacial transition yielding a decreasing ice volume and a rising bedrock elevation of the order of several centimetres per year. The Greenland Ice Sheet was found to be close to a stationary state with a mean thickness change of only a few millimetres per year, but the calculations revealed large spatial differences. Predicted patterns over Greenland are characterized by a small thickening over the ice sheet interior and a general thinning of the ablation area. In Antarctica, almost all of the predicted changes are concentrated in the West Antarctic Ice Sheet, which is still retreating at both the Weddell and Ross Sea margins. Over most of both ice sheets, the model indicates that the surface elevation trend is dominated by ice thickness changes rather than by bedrock elevation changes.
Keywords: Antarktis; glasiologi; innlandsis; polarområdene

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

A study of the ice dynamics of Jutulstraumen drainage area, by means of remote sensing - Rolstad, Cecilie; Hagen, Jon Ove; Østen, Kristoffer; Tonning, Tore; Semb, Svein Ingar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Antarktis; NARE 1997/98; akkumulasjon; glasiologi; innlandsis; klimaendringer

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Report of the Norwegian Antarctic Research Expedition 1997/98 - Tveraa, Torkild (ed.); Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1999)
Keywords: Antarktis; NARE 1997/98; biologi; geodesi; glasiologi; oseanografi

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Report of the Norwegian Antarctic Research Expedition 1993/94 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1996)
Keywords: Antarktis; NARE 1993/94; geodesi; glasiologi; ornitologi

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi

Spatial and temporal patterns in snow accumulation, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Journal of Glaciology, 1994)
During the Swedish Antarctic Expedition to Dronning Maud Land, Antarctica, 1988–89 the net accumulation was estimated for an area from the coast to about 400 km inland. Stake measurements were used to obtain the spatial variability and firn cores were used for the temporal variability. The mean annual accumulation for the period 1976–88 is about 0.4mw.e. for Riiser-Larsenisen and about 0.3mw.e. for the area above the grounding line. The accumulation rate at higher altitudes, > 2500 m a.s.1., is about 0.1 m w.e. for 1955–88. One record from the ice shelf covers the period 1957–88, and suggests an increase in accumulation of about 12%. Between 1976 and 1988, the accumulation has decreased by about 50%, most likely due to lower temperatures as suggested by the temperature record from Halley.
Keywords: Dronning Maud Land; glasiologi

Report of the Norwegian Antarctic Research Expedition 1991/1992 - Østerhus, Svein (ed.) (Norsk Polarinstitutt, 1994)
Keywords: Antarktis; NARE 1991/92; fugler; geologi; glasiologi; ornitologi; oseanografi

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Proximal sub ice-shelf sedimentation Jutulgryta, East Antarctica - Solheim, Anders (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; glasiologi; isshelf

Spectral bi-directional reflectance of snow and glacier ice measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1994)
Visible and near-infrared spectral reflectances of snow and superimposed ice were measured in Dronning Maud Land, Antarctica, during the 1992-93 austral summer. Spectral-reflectance curves of both snow and superimposed ice remain high ( > 80%) in the visible region. A pronounced decrease in reflectance appears in the near-infrared, especially for superimposed ice. Superimposed ice with a 1 cm thick surface layer of ice-bound snow crystals had a considerably higher reflectance than superimposed ice containing only a few snow crystals. Furthermore, these data prove that snow and superimposed ice reflect solar radiation specularly and suggest that the anisotropy strengthens with increasing wavelengths. Integrated in-situ reflectances corresponding to Landsat TM bands 1-4 show that TM band 1 is least affected, whereas TM band 4 is most affected by anisotropy. Furthermore, the anisotropy increases with increasing off-nadir viewing angles up to an angle corresponding to 90°-θs (θs = solar elevation). For a 15° off-nadir sensor-observation angle, the average snow reflectance for TM bands 1--4 is about 10% higher than at nadir. Similarly, the apparent reflectance can be more than 50% higher than the nadir reflectance for larger observation angles. Consequently, if satellite-derived reflectances are going to be considered as absolute values, a topographic-correction model is needed to correct for the effects of anisotropy.
Keywords: Dronning Maud Land; glasiologi

Do glaciers tell a true atmospheric CO2 story? - Jaworowski, Zbigniew; Segalstad, Tom Victor; Ono, Nobuo (Science of The Total Environment, 1992)
Until 1985 most studies of CO2 in gas inclusions in pre-industrial ice indicated that CO2 concentrations (up to 2450 ppm) were higher than the current atmospheric level. After 1985, lower pre-industrial CO2 values were reported, and used as evidence for a recent man-made CO2 increase. The errors in these revised values, however, are of a similar magnitude to the apparent increase in atmospheric CO2 level. The assumptions used in estimating lower CO2 values in past atmospheres have been: no liquid phase in polar ice; younger age of air than of ice due to free gas exchange between deep firn and the atmosphere; and no change in composition of air inclusions. These assumptions are shown to be invalid. Liquid saline water exists in ice at low temperatures, even below −70°C; airtight ice layers are ubiquitous in Antarctic firn; and more than 20 physico-chemical processes operating in situ and in ice cores contribute to the alteration of the chemical composition of air inclusions. The permeable ice sheet with its capillary liquid network acts as a sieve which redistributes elements, isotopes, and micro-particles. Thirty-six to 100% of air recovered from old ice is contaminated by recent atmospheric air during field and laboratory operations. The value of ∼290 ppm, widely accepted from glacier studies for the pre-industrial atmospheric CO2 level, apparently results from: invalid assumptions; processes in ice sheets; artifacts in ice cores; and arbitrary rejection of high readings. To date, glaciological studies are not able to provide a reliable reconstruction of either the CO2 level in pre-industrial and ancient atmospheres or paleoclimates. Instead these studies have led to a widely accepted false dogma of man-made climatic warming. This dogma may have enormous negative impact on our common future.
Keywords: Antarktis; drivhuseffekt; glasiologi; global oppvarming; isbreer; karbondioksid; paleoklimatologi; stabile isotoper

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi

Iceberg scouring and sea bed morphology on the eastern Weddell Sea shelf, Antarctica - Lien, Reidar; Solheim, Anders; Elverhøi, Anders; Rokoengen, Kare (Polar Research, 1989)
Keywords: Antarktis; glasiologi; havbunnen; isberg; isshelf; kontinentalsokkel; morfologi; seismologi

Former extension of the East Antarctic Ice Sheet - Lundqvist, Jan (Polar Research, 1989)
Keywords: Antarktis; geologi; glasiologi; innlandsis

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Antarctic icebergs: production, distribution and disintegration (abstract) - Orheim, Olav (Annals of Glaciology, 1988)
A programme of systematic iceberg observations was initiated in 1981 by Norsk Polarinstitutt through the SCAR Working Group on Glaciology. Icebergs are recorded every 6 h and in five length groups: 10-50, 50-200, 200-500 and 500-1000 m, and those over 1000 m, which are described individually. Data on more than 100 000 icebergs are now on file at Norsk Polarinstitutt, and practically all ships travelling to and from Antarctica participate in the collection of data. This paper presents the first comprehensive analysis of the iceberg data. The quality of the data set is discussed, with consideration of potential errors in and limitations of the data, and various statistical evaluations. Representative distribution data are presented, and used to determine iceberg production, disintegration and mean residence times, and regional and total Antarctic calving rates. The incidence of large-scale calving in particular is evaluated, including the remarkably large break-offs in recent years. These exceed both the total annual accumulation on the Antarctic continent and the mean annual calving rate as determined from ship observations. The results show further: (1) that there are more than 200 000 icebergs south of the Antarctic Convergence, (2) that there are large regional differences in iceberg calving rates and iceberg sizes, and (3) that the calving rate from Antarctica is higher than that given in most previous estimates, which implies (4) that the mass balance of the Antarctic ice sheet is not positive as suggested by most recent estimates.
Keywords: Sørishavet; glasiologi

Numerical Analysis of Landsat Thematic Mapper Images of Antarctica: Surface Temperatures and Physical Properties - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1988)
Keywords: Dronning Maud Land; glasiologi; innlandsis; satellittbilder; topografi

Evolution of under water sides of ice shelves and icebergs - Orheim, Olav (Annals of Glaciology, 1987)
A systematic programme of side-scan sonar and plumb- line soundings was carried out in the Weddell Sea area in 1985 to measure the under-water sides of ice shelves and icebergs. From these observations the following model is suggested for the evolution of the ice front: (1) Initial stage: fracturing of the ice shelves takes place along smooth, curvi-linear segments with vertical faces. (2) Formative stage: the freshly formed vertical face is eroded both by wave and swell action around the water line, by small calvings from the undercut, overhanging subaerial face, and by submarine melting. The melting has a minimum at 50–100 m depth, and increases with depth to a rate of around 10 m a−1 at 200 m, This is about twice the rate of erosion at the water line. The variation in melting with depth results from a combination of summer melting by near-surface water, and year-round melting by water masses that are increasingly warmer than the pressure melting-point with depth. (3) Mature stage: this stage is reached after a few years of exposure. The backward erosion of the face leads to a shape with a prominent under-water “nose” with a maximum projection to more than 50 m at 50–100 m depth. The ramp above this slopes upwards to meet the vertical wall about 5 m below the water line. The ice below the nose is melted back beyond the above-water face. There is no net buoyancy and ice shelves at this mature stage are generally not up-warped at the front.
Keywords: Sørishavet; glasiologi

Icebergs in the Southern Ocean (abstract) - Orheim, Olav (Annals of Glaciology, 1987)
Relatively little data on the distribution of Antarctic icebergs were available prior to 1980. The published literature included size data of about 5000 icebergs, and position data of 12 000 icebergs. There were indications that the size data were biased in favour of larger icebergs. A programme of systematic iceberg observations was therefore initiated by Norsk Polarinstitutt in 198! through the SCAR Working Group on Glaciology. This programme is based on standard “blue” forms distributed to all ships going to Antarctica. The icebergs are recorded every 6 h and in Five length groups: 10–50, 50–200, 200–500, and 500–1000 m, and those over 1000 m are described individually. The amount of data has increased greatly from the start in 1981–82. The position of 70 000 icebergs, including 50 000 that had been size classified, were on file at Norsk Polarinstitutt by December 1985, and the data set is growing rapidly. Most ships travelling to and from Antarctica now participate in collection of the data. ( shows the locations of the icebergs sighted.) Fig. 1. Location of iceberg observations under the programme initiated in 1981. Main ship tracks are clearly reflected. The average observation represents 14 icebergs. The size distribution of the classified icebergs observed under this programme up to December 1985 is given in : Table I The “standard size” (length, width, and thickness) is based on our observations from three Antarctic expeditions which carried out dedicated iceberg studies. Many icebergs are of course not right-angled parallelepipedal in shape, but this is a good approximation for most of the larger icebergs. The data are based both on visual sightings and on radar observations. Duplicate observations from a ship moving at slow or zero speed are as far as possible eliminated, both during observation, and by critical appraisal before the data are filed. The data editing also includes evaluation of data quality, especially in connection with radar observations, and comparison of positions and dimensions of the large icebergs in order to reduce to a minimum repeated observations from different vessels of icebergs >1000 m. These account for most of the iceberg mass (see ). Consideration of iceberg-distribution patterns and the observed area of the Southern Ocean, and of duplicate observations, indicates more than 300 000 icebergs south of the Antarctic Convergence, with a total ice mass of about 1016 kg. Consideration of mean residence times indicates an annual iceberg production from the continent of 23–1015 kg, which is considerably higher than most other recent estimates. This also suggests that the Antarctic ice sheet is in balance. The data indicate large regional differences in iceberg sizes, the most noticeable being between the two sides of the Antarctic Peninsula, and between the Amery Ice Shelf/ Prydz Bay area and the remainder of East Antarctica. These differences are probably mainly related to different calving sites. About one-third of the observed icebergs are over the continental shelf of Antarctica. The total under-water area of these icebergs is two orders of magnitude less than the under-water area of the Antarctic ice shelves. The annual total iceberg melting and its effect on the water masses over the continental shelf has been calculated from ocean-water temperature variations at 200 m depth and estimated melt rates. This turns out to be an order of magnitude less than the annual effect of melting sea ice. The iceberg data considered here are probably under-represented with respect to the smallest sizes, and they do not include icebergs that have become <10 m. Inclusion of these ice bodies would increase the total melt.
Keywords: Sørishavet; glasiologi

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Flow and thickness of Riiser-Larsenisen, Antarctica - Orheim, Olav; Drewry, David (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; glasiologi; isshelf

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Meteorological and glaciological studies in Dronning Maud Land - Gjessing, Yngvar (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; glasiologi; meteorologi

Geomorphological and glaciological observations in Vestfjella, Dronning Maud Land - Jonsson, Stig (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; geomorfologi; glasiologi

Iceberg research and other glaciological studies from K/V "Andenes" - Kristensen, Monica; Orheim, Olav (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; glasiologi; isfjell

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Iceberg calving and deterioration in Antarctica - Kristensen, Monica (Progress in Physical Geography: Earth and Environment, 1983)
Keywords: Antarktis; glasiologi; innlandsis; isbreer; isbrem; kalving

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer

Evidence for a late Wisconsin glaciation of the Weddell Sea - Elverhøi, Anders (Nature, 1981)
Keywords: Sørishavet; Weddellhavet; forskning; glasiologi; sedimentologi; stratigrafi

Glaciomarine sediments and suspended particulate matter, Weddell sea, Antarctica (abstract only) - Elverhøi, Anders; Roaldset, Elen (Annals of Glaciology, 1981)
Samples of glaciomarine sediments and suspended particulate matter filtered from sea-water were collected in the Weddell Sea during the Norwegian Antarctic Research Expedition (NARE) in 1978–79. Analyses have provided information on the textural and mineralogical composition of shelf sediments, on the nature of biogenic and inorganic suspended particulate matter, and on the total sediment transport to the shelf areas and further into the deeper waters (). The shelf waters contain 0.1 to 1.2 g m–3 of suspended particulate matter, which is close to the range of 0.5 to 1.5 g m–3 reported for suspension concentrations in the oceans, but considerably lower than that found for some other glaciomarine environments such as the Bering Sea {up to 13-15 g m–3 ()) and off Kongsbreen, Spitsbergen {up to 500 g m–3 ()). Suspended particles from the Weddell Sea have maximum sizes of 50 to 70 µm and mean diameters in the range of 10 to 20 µm. In contrast, the bottom sediments on the outer shelf are deficient in the corresponding fractions. This reflects that when floating Antarctic ice supplies material to the Weddell Sea, the coarser fragments (>20-70 µm) are deposited, while the medium silt and finer fractions go into suspension. Considering the suspended-load data and the bottom-current measurements on the shelf break, it is evident that in January 1979 an average of 8.6 × 104tonnes d–1 (or 32 × 106 tonnes a–l) of particulate matter was transported by the current from the central Weddell Sea to the South Atlantic deep water. Morphological (scanning electron microscopy) and chemical analyses show the suspended material to be dominated by silica organisms (diatoms), and also to contain clastic grains of phyllosilicates, feldspar, quartz, zircon, in a few cases Al- and Fe-hydroxides/oxides also; authigenic “Fe-sepiolite” and secondary gypsum. Mineralogical analyses (X-ray diffraction) of the bottom sediments show the fine sand silt fractions to contain mainly clastic materials like illite, smectite-vermiculite, and quartz. Biogenic silica (cristobalite) and carbonate (Mg-calcite) as well as authigenic Fe-silicates (“Fe-sepiolite”) are also present.
Keywords: Sørishavet; glasiologi; sedimenter

The glaciers of Bouvetøya - Orheim, Olav (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; glasiologi; isbreer

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Snow accumulation and snow stratigraphy on Riiser-Larsenisen, Dronning Maud Land, Antarctica - Repp, Kjell (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; geologi; glasiologi; isshelf; snø; stratigrafi

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Innsjøer under isen i Antarktis - Fægri, Knut (Naturen, 1973)
Keywords: Antarktis; geofysikk; glasiologi

Mass transport of Jutulstraumen ice stream in Dronning Maud Land - Gjessing, Yngvar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; ekspedisjoner; glasiologi; isbreer; isstrøm

Diurnal variations of the surface wind over the Antarctic ice shelf - Hisdal, Vidar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

Diurnal wind variations in Antarctica - Hisdal, Vidar (Quarterly Journal of the Royal Meteorological Society, 1972)
For the three Antarctic ice shelf stations considered (Norway Station, Maudheim, and Halley Bay) it is shown that from spring to autumn a systematic diurnal variation of the mean vector wind at the surface exists. Different factors that may be responsible for this variation are discussed. The results seem to agree well with the assumption that in areas far from the ice front (the seaward edge of the ice shelf) the main cause is the larger net gain of momentum in the lowest layers during the middle of the day, while closer to the ice front there is an additional effect of the varying contrast between the air temperature over the sea and over the ice shelf.
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi

The Norwegian Antarctic Expedition 1970-1971 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1970-71; biologi; geologi; glasiologi

The Norwegian Antarctic Expedition 1968-69 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1968, 1970)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1968-69; biologi; geologi; glasiologi

The turbulent transfer over an Antarctic ice shelf - Vinje, Torgny E. (Norsk Polarinstitutt, 1969)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; glasiologi; isshelf

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi

Studies of surface snow at Plateau station - Lunde, Torbjørn (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; ekspedisjoner; firnsnø; forskning; glasiologi; metamorfologi; morfologi; snø; stratigrafi

Studies of surface snow at Plateau Station - Orheim, Olav (Antarctic Journal of the United States, 1968)
Keywords: Dronning Maud Land; glasiologi; snø; stratigrafi

Surface snow metamorphosis on the Antarctic Plateau - Orheim, Olav (Norsk Polarinstitutt. Årbok 1966, 1968)
Keywords: Dronning Maud Land; firnsnø; glasiologi; metamorfologi; stratigrafi

Some results of micrometeorological measurements in Antarctica - Vinje, Torgny E (Archiv für Meteorologie, Geophysik und Bioklimatologie, Serie A, 1967)
Keywords: Dronning Maud Land; glasiologi; meteorologi

Fra Sydpolen til "Utilgjengelighetens pol" (From The South Pole to The Pole of Inaccessibility) - Dybvadskog, Olav (Norsk Polarinstitutt. Årbok 1964, 1966)
Keywords: Antarktis; ekspedisjoner; forskning; glasiologi; gravimetri; meteorologi; observasjoner; seismologi

Fra et besøk på Bouvetøya - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Bouvetøya; geologi; glasiologi

On the firn temperatures and glacier flow in Dronning Maud Land - Lunde, Torbjørn (Norsk Polarinstitutt. Årbok 1963, 1965)
Keywords: Dronning Maud Land; firnsnø; glasiologi; isbreer; isstrøm

Annen etappe av Dronning Maud Land Traversen - Orheim, Olav (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; glasiologi; gravimetri; meteorologi; seismologi

Note on occurence of limburgite in Dronning Maud Land, Antarctica - Gjelsvik, Tore (Norsk Polarinstitutt. Årbok 1960, 1962)
The rocks from Dronning Maud Land, collected by T. LUNDE along 72° S and between 3° W and 7° E are mostly ordinary gneisses. However, a black, basaltic rock, apparently belonging to a sil! or a dyke has been found on Jutulsessen. The rock is lacking feidspar and consists only of augite, olivine, devitrified glass, and accessories. The chemical composition of the rock, mode and norm are given in table I. The present investigation shows that the Antarctic limburgite seems to be related to the normal olivine basalts, and not to the derivates of the basanite series.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geologi; glasiologi

The volume of ice in Antarctica - Liestøl, Olav (Norsk Polarinstitutt. Årbok 1961, 1962)
At present c. 15 mill. km• of the earth's surface is covered with ice. Of this area about 85 % falls to the account of Antarctica, 11 % to Greenland and c. 4 % to other areas. From this it is evident that a good knowledge of the ice mass of Antarctica is a deciding factor for the calculation of the total ice volume on earth and its effect on eustatic changes.
Keywords: Dronning Maud Land; glasiologi; havis; havnivåstigning; sjøis

Maudheim Revisited: The Morphology and Regime of the lce Shelf, 1950-1960 - Swithinbank, Charles (Norsk Polarinstitutt. Årbok 1960, 1962)
Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition, 1949-52, (71° 02' S, 10° 56' W) was revisited in January 1960 by the Norwegian Antarctic Expedition, 1956-60 under the leadership of SIGURD HELLF.. HELLE has very kindly made his observations available to me and has read the manuscript of this note. The work of his party gives a reliable measure of the accumulation of snow at Maudheim from 1952 to 1960 and allows a hetter estimate of the bottom melting on the ice shelf than was possible from the 1950-52 measurements. Air photographs taken in December 1958 by B. LuNCKE show the extent of changes in the ice front since 1951.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Determination of the Thickness of Ice Shelves by Seismic Shooting Methods - Robin, Gordon de Quetteville (Nature, 1956)
SEISMIC soundings of the thickness of the floating ice shelves of Antarctica have so far been attempted by two expeditions, the Second Byrd Antarctic Expedition of 1933–35 1, and the Norwegian–British–Swedish Antarctic Expedition 1949–52 2,3. Further measurements are likely to be made by several expeditions during the International Geophysical Year 1957–58. Reinterpretation of results from iceshelves obtained from the Norwegian-British-Swedish Antarctic expedition 1949-52.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Et forsøk på måling av breforandring i Antarktis - Liestøl, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1954)
Keywords: Antarktis; glasiologi; isbreer; klimaendringer

Measurements of ice thickness in Dronning Maud Land - Robin, Gordon de Quetteville (Polar Record, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi

Measurements of Ice thickness in Dronning Maud Land, Antarctica - Robin, Gordon de Quetteville (Nature, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; glasiologi

The currents of the coast of Queen Mauds Land - Sverdrup, Harald Ulrik (1953)
Keywords: Dronning Maud Land; glasiologi; havstrømmer; isshelf

Preliminary Glaciological Plans for the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Ahlmann, Hans Wilhelmsson (Journal of Glaciology, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; glasiologi